Evaluasi Usability Sistem Informasi Akademik Dosen Menggunakan User Experience Questionnaire dan Heuristic Walkthrough - Yuslena Sari; Maulidia Arafah; Novitasari (Ikatan Ahli Informatika Indonesia (IAII), 2021)
University of Lambung Mangkurat (ULM) has an academic information system that can facilitate access to information and provide quality academic services. One of the ULM academic information system services is the Portal Akademik Dosen ULM. Since its release in 2016, there has been no research regarding the evaluation of the Portal Akademik Dosen ULM. Most of users feel that the interface of the Portal Akademik Dosen ULM needs to be improved to make it more attractive, and needs improvements in several features. In connection with the important function of the Portal Akademik Dosen ULM, an evaluation is needed to assess the success of implementing the information system. This study aims to evaluate the usability of the Portal Akademik Dosen ULM. The methods used are the User Experience Questionnaire (UEQ) and Heuristic Walkthrough. Based on the results of the UEQ questionnaire from 56 respondents, it was found that the aspects of attractiveness, perspicuity, efficiency, dependability, and stimulation got positive values, while the novelty aspect got a neutral value. For the evaluation results with Heuristic Walkthrough method which involved 4 evaluators, found 33 problems at the Cognitive Walkthrough stage, and as many as 21 problems at the Heuristic Evaluation stage with an average severity rating of 13.4. The overall results of the evaluation showed that the Portal Akademik Dosen ULM needs to be improved on novelty items and need to be improved to reduce the number of problems.